Making sense of ultra-realism : contemporary criminological theory through the lens of popular culture - Kotzé, Justin; Lloyd, Anthony (Emerald Publishing Limited, 2022)
Making Sense of Ultra-Realism offers readers a unique insight into one of the most significant theoretical advances in 21st century criminology. Drawing upon popular films and television series, including Game of Thrones, Avengers, Pirates of the Caribbean, Fight Club and more, each chapter tackles a particular aspect of ultra-realism. By connecting visual texts to theoretical ideas, the authors help to contextualise and clarify core elements of the ultra-realist school of thought, providing a theoretically rich yet accessible introduction to the topic. Often wrongly viewed as opaque and impenetrable, this concise text demonstrates that ultra-realism is anything but that. Written in a clear and accessible manner, and supported by valuable student insights, this book is ideal for those coming to the subject for the first time. This timely addition to a cutting-edge field is undoubtedly a 'must read' on the reading lists of a number of undergraduate and postgraduate courses, as well as a helpful resource for experienced academics in the fields of criminology, social policy, politics, psychology, philosophy, and sociology.
Keywords: Criminology.; Social Science -- Criminology.; Crime & criminology.; elektronické knihy; electronic books